MORFOLOGIA DOS ÓRGÃOS GENITAIS MASCULINOS EM ADULTOS DE Podocnemis unifilis (TESTUDINES: PODOCNEMIDIDAE) - FIRMINO, Maria (Instituto Nacional de Pesquisas da Amazônia - INPA, 2025)
There are approximately 361 species of turtles worldwide, distributed across tropical and subtropical regions. In Brazil, there are 37 species, with 21 species specifically found in the Amazon region. Turtles play a significant ecological role as seed dispersers, contributors to organic matter cycling, and prey for other animals. Among the Amazonian species, Podocnemis unifilis, commonly known as the tracajá, is one of the most widely distributed species within the Podocnemis genus. This study aimed to describe the morphology of the male genital organs of Podocnemis unifilis and their macroscopic and histological aspects. Sixteen specimens deposited in the collection of the National Institute of Amazonian Research were used. Of the 16 individuals, 11 exhibited active spermatogenesis, 1 did not, and for 4, visualization was not possible. Male specimens of Podocnemis unifilis had an average carapace length of 220±2.06mm, featuring a pair of testicles, epididymides, vas deferens, and a phallus. The testicles had a yellowish coloration with an elongated shape and a thin cranial end. Histologically, the testicles were encapsulated by fibrous tissue containing seminiferous tubules with circular shapes, comprising a significant portion of the testis, with cells at different stages of spermatogenesis. The male genital organs of Podocnemis unifilis share similarities with those of other turtle species.
Keywords: Morfologia; Quelônios